The Use of Teat-End Hyperkeratosis to Predict Somatic Cell Count and Milk Quality of Holstein Cows Raised in Egypt - S. Abdelghany; N. Fahim; F. Samir; M. Radwan (Tropical Animal Science Journal, 2021)
The study aimed to investigate the association between teat-end hyperkeratosis (THK) and somatic cell count (SCC) and to assess the effect of SCC on milk yield, fat, and protein percentages of Holstein cows. A total of 740 udder quarters of 185 Holstein cows kept in three commercial herds in Egypt were enrolled in the study from May to September 2019. Foremilk samples were collected from udder quarters for assessing milk SCC, fat, and protein percentages. On the same cows, a digital picture of each teat end orifice was taken with a digital camera. Cows’ teats were assessed for THK and classified into two different groups of hyperkeratosis; mild and severe THK. SCC was converted to five classes of somatic cell score (SCS). Simple linear regression was performed to determine the loss of milk yield, fat, and protein percentages. SCC was significantly affected by THK (p<0.0001). About 57% of teats were classified as mild THK and 43% as severe THK. The teats with severe THK recorded higher SCC in milk. It was observed that SCS had a significant effect on fat and protein percentages (p<0.0001). A similar trend was shown for the effect of SCS on milk yield (p<0.05), where the highest values of milk traits were obtained for the lowest SCS. The loss of milk was 220 g/day. Also, fat and protein percentages decreased by 0.11% and 0.08%, respectively, for each unit increase in SCS, from zero to four. In conclusion, severe THK can lead to high SCC, which negatively affects milk traits.